Het Apollohuis 1980-1985 : vijf jaar tentoonstellingen, concerten, performances, installaties, lezingen, publicaties. - Panhuysen, Paul; Yocarini, Titus; Het Apollohuis, Eindhoven (Eindhoven : Het Apollohuis, 1985)
Panhuysen, Paul ; Goedhart, Johan ; Longo, Robert ; Bogosian, Eric ; Z'ev ; Jean, Barbara ; Fick, Mario ; Smith, Michael ; Oosthoek, Piet ; Scha, Remko ; Visch, Henk ; Branca, Glenn ; Kaplan, Morton ; Weisser, Stefan ; Daniels, René ; Persoon, Kars ; de Kroon, Harrie ; van Keulen, Floor ; Broos, Lotte ; de Vries, Herman ; Robakowski, Jozef ; Potocka, Margarit ; de Ridder, Willem ; van der Linden, Thomas ; MacLow, Jackson ; van den Dobbelsteen, Jan ; van den Dobbelsteen, Gerard ; Van Kleef, Diederick ; Altena, Maarten ; Smejkal, Jan ; Sachsse, Rolf ; Hörl, Ottmar ; St. James, Marthy ; Wilson, Anne ; Gribling, Frank ; Abma, Harmen ; Hansma, Siebe ; Oosthoek, Piet ; Horvers, Toine ; O'Pezzati, Mark ; Steven, Leslie ; Morris, Philip ; CWM Dolk ; Nolte, Titus ; Sips, Roland ; Dierman, Jan ; Puckey, Tom ; Blake, John ; Hendriks, Berend ; Terwindt, Eugène ; O'Brien, Robert ; Auer, Olaf ; Charlier, Jacques ; Postema, Dick ; Raaymakers, Dick ; Koenings, Christine F. ; Rothenberg, Erika ; Kersten, Willem Jan ; Shaw, Jeffrey ; van Noorden, Leon ; Cypis, Dorit ; Körmeling, John ; Scha, Remko ; Bennink, Han ; Dura, Thom ; Pelgrom, Karl ; Latham, John ; Bodde, Jan ; Koopman, Eduard ; Beckmans, F.F. ; Vugts, Yntse ; Siegrist, Roland ; Kubiczak, Harald ; Roothaan, Steef ; de Vries, Herman ; Rombouts, Guy ; Deleu, Luc ; Berghe, Roland Van Den ; Oelen, Henk ; van Meeuwen, Hans ; Koek, Gerard ; de Quasa Riera, Fabienne ; Barrio, Artur ; Deguchi, Michiyoshi ; Mulacami, Yasuhilo ; van der Weide, Albert ; Smits, George ; Wonders, José ; Barry, Judith ; Baren, Peter ; Johnson, Tom ; van Iersel, Rik ; Laurense, Toon ; Medalla, David ; Hilgemann, Kai ; Mol, Pieter Laurens ; Moorees, Rob ; van den Boom, Herman ; Micholajczyk, Antoni ; Koenraads, Guus ; Fitzsimons, Connie ; etc.
Overzicht
Nederlands
boek